Management Von Teams 2005
DOI: 10.1007/978-3-322-81926-0_7
|View full text |Cite
|
Sign up to set email alerts
|

Individuelle Autonomie in Projektteams

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…In this context, a study conducted revealed support for the role of self-leadership expertise in fostering innovative behaviour at Project managers and employees' leaderships work (Carmeli et al, 2006). Haberstroh (2007) shows that the self-leadership of team members improves project performance. Such a project leader consults followers to enhance their self-leadership and encourages them for this purpose.…”
Section: Self-leadership and Project Successmentioning
confidence: 99%
“…In this context, a study conducted revealed support for the role of self-leadership expertise in fostering innovative behaviour at Project managers and employees' leaderships work (Carmeli et al, 2006). Haberstroh (2007) shows that the self-leadership of team members improves project performance. Such a project leader consults followers to enhance their self-leadership and encourages them for this purpose.…”
Section: Self-leadership and Project Successmentioning
confidence: 99%